A Comparative Study of the Microleakage of Resilon/Epiphany and Gutta-Percha/AH-Plus Obturating Systems - Fathia, Elmakki; Abu-bakr, Neamat Hassan; Yahia, Ibrahim (Iranian Endodontic Journal, 2012)
Introduction: The aim of the present study was to investigate and compare the apical sealing ability of Resilon/Epiphany-filled root canals with those that were obturated with gutta-percha/AH-Plus endodontic sealer. Materials and Methods: A total of 60 extracted human single-rooted teeth were selected; 25 teeth for each test group and five for each control group. After conducting conventional endodontic treatment, the teeth were immersed in physiologic saline solution for thirty days, and subsequently sealed and stored in methylene blue dye solution for seven days. The teeth were sectioned to evaluate the linear apical leakage using a stereoscopic microscope. The data were statistically analyzed by non-parametric Kruskal-Wallis and Mann-Whitney U tests. Results: The results showed significant differences between the two groups of endodontic sealers (P<0.001). Conclusion: Within the limitation of the present in vitro study, Resilon/Epiphany sealer had better apical sealing ability than gutta-percha/AH-Plus sealer.